Estudo tomográfico das variações anatômicas do canal mandibular, com ênfase no loop anterior e forame mentual acessório - VIEIRA, Clarissa Lopes (2018)
The location of the mandibular canal is important in dentistry, since anatomical variations in its path may impair the anesthetic block of the inferior alveolar nerve, the planning of dental extractions, orthognathic surgeries, implant placement, and removal of bone grafts. The occurrence of these variations has already been addressed in literature, both by studies using panoramic radiographs and cone beam computed tomography (CBCT). Thus, the aim of this study was to verify the occurrence of anatomical variations of the mandibular canal through the analysis of cone beam tomographic images of a Dental Radiology clinic in the city of São Luís – MA. This thesis is composed of two chapters, written in the form of scientific articles, related to the preliminary results of the evaluation of CBCT images of 480 hemimandibles. In the first chapter, the aim was to determine the prevalence of mandibular canal paths, the presence of anterior loop and the accessory mental foramen, as well as to verify the association between these variables. Data analysis showed that the most prevalent type of mandibular canal path was the rectus type and prevalence of anterior loop and accessory foramen similar to that recorded in literature was found. No association was found between mandibular canal path and presence of anterior loop and the accessory mental foramen. In the second chapter, the aim was to verify the occurrence of anatomical variations of the mandibular canal (canal course, anterior loop and accessory mental foramen) and its association with dental loss. Data analysis showed that bone changes due to dental loss influenced the course of the mandibular canal and in the maintenance of the anterior loop and the accessory mental foramen, when they exist. Preliminary results have shown that, once anatomical variations are detected, regardless of whether or not there is dental loss, the dentist needs to evaluate them through appropriate imaging examinations, thus avoiding possible injuries or postoperative complications. In this case, CBCT seems to be a good indication for the planning of surgical procedures.